Effectiveness of Compassionate Mind-Based Cognitive Therapy on Adolescents' Behavioral Activation-Inhibition Systems and Theory of Mind - Dehghan, Hamidreza; Naderi, Habibollah; Baezzat, Fereshteh; Hashemi, Soheila (International Journal of Applied Behavioral Sciences, 2022)
Background and Aim:High-risk behaviors have devastating physical, psychological, and social consequences for the adolescents. This study aimed to investigate the effectiveness of compassionate mind-based cognitive therapy on behavioral inhibition-activation systems and the theory of mind of adolescents with high-risk behaviors. Materials and Methods:The study design was quasi-experimental with control and intervention groups and a follow-up phase.The statistical population included all high school boys with high-risk behaviors in Tabriz. The sample consisted of 30 students who were purposefully selected, and randomly allocated into experimental and control groups. High-Risk Behaviors Questionnaire, Brain-Behavioral Systems Scale, and the Theory of Mind Questionnaire were used to collect data. Data were analyzed using multivariate analysis of variance test and employing SPSS-24 software. Results:Compassion-focused cognitive therapy decreased activation, increased inhibition, and improved theory of mind among adolescents with high-risk behaviors (P<0.01). Conclusion:Based on the findings of this study, it can be concluded that cognitive therapy based on compassionate mind through the component of mindfulness by reducing rumination, leads to a reduction of negative emotions and thus reduces high-risk behaviors in adolescents. Thus, it can be said that treatment based on Compassion can be used as an effective treatment to improve adolescent psychological problems with high-risk behaviors.